Acute-on-chronic liver failure due to thiamazole in a patient with hyperthyroidism and trilogy of Fallot: case report - Shen, Chuan (BioMed Central, 2010)
BACKGROUND: Thiamazole is a widely used antithyroid agent that has been approved for the treatment of hyperthyroidism. Although thiamazole-induced hepatotoxicity is a main side effect, it may progress to liver failure in a very few cases. CASE PRESENTATION: We described a 24-year-old patient with hyperthyroidism and trilogy of Fallot, who developed liver failure due to thiamazole. Liver biopsy showed intrahepatic cholestasis, mild inflammatory infiltrates, as well as significant fibrosis, indicating both acute and chronic liver injuries. Although a series of potent therapies were given, the patient deceased due to severe liver decompensation. CONCLUSIONS: This case suggests that thiamazole-induced hepatotoxicity in the setting of advanced fibrosis increases the risk of poor outcome. Regular liver function monitoring during thiamazole therapy is therefore important.